Evaluating Founders of Start-Up Companies When Business Angels Decide on Investment - Levs FAINGLOZS (Communications of International Proceedings, 2020)
Business angels’ investments are an important funding source of start-up companies at the earlier stages of development. Analysing the existing scientific literature in terms of the investment criteria applied by business angels made it possible to identify more than 200 various criteria.  Within the framework of this study, in view of so large number of investment criteria, the author has decided to consider only the criteria applied by business angels to start-up company founders. This was decided because most of the previous studies authors singled out exactly the entrepreneur and the team as the most important criterion. At the same time, note that these authors used to make only qualitative assessment by comparing between the investing criteria. That is why the goal of this research is: making quantitative assessment and defining the level of assessment of start-up company founders at which business angels are ready to invest in the start-up company. To achieve the goal of the study, a survey took place among 118 business angels with different investment experience. The analysis of the survey has revealed that the most significant criterion for business angels making decision on investing is trust the founders - regardless of the business angels’ experience, while the least significant criterion is the managerial skills of start-up founders. Moreover, it was stated that, with the growth of investment experience, the requirements of business angels to start-up founders are becoming more stringent.
Keywords: Business Angels; Founder’s Assessment; Investment Criteria